Study abroad benefits and graduates employability: Asian International Mobility for Students Programme (AIMS): Malaysia - Nordiana Mohd Nordin,; Fiffy Hanisdah Saikim,; Jamshed Khalid,; Anees Janee Ali,; Azman Mat Isa,; Norizan Anwar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The multitude of existing research conducted within the field of study abroad generally reinforces the popular understanding that the practice not only broadens the mind, provides valuable experiences and enhances stagnating perspectives, but also contributes to a skillset that is becoming increasingly necessary for success in the globally focused world of today. Despite the evidence supporting their effectiveness, relatively few undergraduate students of Malaysia choose to participate in some form of study abroad programmes especially to the ASEAN countries. The following analysis will examine the potential reasoning of why this is so. In this context the focus is on the mobility programme on the short-term exchange and study abroad issues. Through the survey, this research examined the attitudes and inhibitions of undergraduate university students as they relate to studying abroad and to what extent these perceptions fall in line with the escalating importance of employability. Used as an exemplifying case of Asian Mobility for Students Programmes (AIMS), ten participating public universities under the AIMS-Malaysia furnished the sample of participants used in this study. Factors such as a student’s previous international travel experience and awareness of available programmes are seen to influence these perceptions to some degree. The students highlighted the benefits of studying abroad as to have better understanding of cultural differences and new friends share the same highest mean. The students also developed their soft skills by being more independent, confident and improve their problem-solving skills. In addition, they also have better communication, self-assessment and personal skills. The finding also showed that the most important criteria that the alumni being hired for their first job after graduation are communication skills, high adaptability, analytical thinking and problem solving. These findings corroborate international student mobility programmes whilst providing additional insight through student testimony. Indeed, AIMS programme leverages the competency and employability of students, hence contributes to producing global citizens and ASEAN harmonization.